Repurposing: Another R to prioritize in data curation. Issue 1 (18th October 2019) - Twidale, Michael; Blake, Catherine; Souden, Maria; Stelmack, Jenifer; Kim, Jenna
ABSTRACT: Data repurposing has great potential for innovative research. But there are distinct risks of researchers outside the group who originally collected the data misunderstanding the actual meaning of particular fields and values. These meanings may not be sufficiently well documented, as those within the collecting group know what is really meant in the context of the original purposes of collection.